A negative emission internal combustion engine vehicle?. (1st February 2023) - Leach, Felix
Abstract: Modern internal combustion engine vehicles carry extensive exhaust aftertreatment systems that have the potential to reduce their tailpipe pollutant emissions to near-zero, or even within the zero levels of measurement equipment in real-world conditions. It has been reported, therefore, that such vehicles have the potential to have tailpipe pollutant levels lower than the air intake of the vehicle – that they are cleaning the ambient air. This study investigates this hypothesis using a range of internal combustion engines and real-world emissions data alongside pollutant (in this case nitrogen dioxide and particulate matter) data from around the world and the accuracy of the instrumentation typically used to measure tailpipe emissions. The results show that it is unlikely that a modern internal combustion engine vehicle will clean ambient air, even at extreme pollution levels, although it is possible. However, where a vehicle inlet is in the plume of a dirtier vehicle or the pollution measured is among the highest values recorded globally, the pollution reduction can be substantial. Highlights: Modern internal combustion engines can have very low pollutant emissions. Some places in the world can have very high levels of atmospheric pollutants. It is possible that modern vehicles can be negative emission. However, the circumstances under which this can happen on average are limited. A spreadsheet tool is available for readers to use their own values.